The Efficacy of Focused and Unfocused Written Corrective Feedback on EFL Learners’ Grammatical Accuracy - Aliakbari, Mohammad; Aryan, Mehdi; Sourani, Maha (Al-Adab Journal, 2023)
The potential effectiveness of various kinds of written corrective feedback (CF) has been the focus of CF investigations that did not reach firm conclusions about which methods of correction can more successfully facilitate students’ grammatical development. A good majority of the studies investigated an unfocused approach to CF while a focused approach has received far less attention. In line with this argument, the current study employed a pre-test, immediate post-test and delayed post-test design and set out to investigate the potential efficacy of unfocused and focused written CF in L2 accuracy development. The study incorporated 86 EFL students allocated to one control group and two experimental groups. Students in the focused group were corrected on irregular and regular past tense, while students in the unfocused group were corrected on a greater range of grammatical categories including irregular and regular past tense as well and learners in the control group received no written CF. Results of two-way repeated measures ANOVA and a set of ANOVAs with post-hoc evaluations revealed that in the short-term duration both treatment groups increased their accuracy but the efficacy of the focused CF found to be resilient.